The Correlation Between Social Support and Adolescent Mental Health Among High School Students in Surabaya - Nur Ainiyah; R. Khairiyatul Afiyah; Riska Rohmawati; Febi Ariska Putri; Ely Rahmawati (Jurnal Ilmiah STIKES Yarsi Mataram, 2026)
Adolescent mental health is an important issue that is often overlooked, especially amidst academic and social pressures. Social support from family, friends, and the environment is believed to help adolescents face these challenges. This study aims to analyse the relationship between social support and mental health in students of Senior High School X Surabaya. The research design used was analytical with a Cross-Sectional approach. The study population comprised all 254 students in grades X and XI, and a sample of 155 students was selected using the Proportionate Stratified Random Sampling technique. The instruments used were the Multidimensional Scale of Perceived Social Support (MPSS) and the Strengths and Difficulties Questionnaire (SDQ). Data analysis was performed using the Spearman Rank test. The results showed that 54.9% of respondents had moderate levels of social support, and 78.7% had mental health in the normal range. Statistical tests showed a significant relationship between social support and mental health (p = 0.047; r = 0.160). It can be concluded that the greater the social support received, the better adolescents' mental health This study recommends strengthening social support through collaboration between families, schools, and health workers as part of promotive and preventive efforts to improve adolescent mental health. This study recomend strengthening social support through collaboration between families, schools, and health workers as part of promotive and preventive efforts to improve adolescent mental health.